A Proposed Quality Measurements for Information Systems Development Projects - Samih Karim Buo-Oga; Mohamed Taher Nour (International Journal of Computers and Informatics, 2024)
The objective of this paper is to propose quality measurements for ISDP to achieve higher quality levels for information systems development projects (ISDP). The complexity of assessing information system quality stems from its many important dimensions. This paper presents important quality concepts and fundamentals related to ISDP. In addition, it presents the life cycle, phases, and activities of ISDP. Depending on the proposed steps and a combination of statistical techniques, this paper introduces a proposed quality assurance model for ISDP activities. This proposed model can be used for building a software tool for the quality assurance of ISDP.